Demokracja i federalizm - Machelski, Zbigniew (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
In terms of law, federation is a complex political, economic, administrative and social system, whose individual components enjoy a significant level of independence. Political authority is organized so as to protect the identity of national, ethnic, linguistic and cultural minorities living in the territory of this multidimensional federal structure. From the constitutional point of view, federalism has two principal functions. Firstly, it unifies a state that was once disintegrated, thus allowing for the establishment of a political union and of some form of authority, which is a prerequisite of forming a somewhat broader identity; alternatively, it unifies various states. This function consists of the unification of what used to be separated and disintegrated. The other function concerns the task of maintaining the unity of those who underline the legitimacy of the authorities and reject their governance, because they feel harmed and oppressed by the political regime, or they believe that their interests are not guaranteed in the framework of a constitutionally determined autonomy. This is usually connected with their striving to become separated. In this case, federalism is a reaction to the threat of the state’s disintegration, when different identities emerge in its internal structure, although they are not mutually excluded, and they do not exclude one another from this state yet. Then, federalism becomes a form of identification of various subjects with the federal state in a broader than local perspective. The second function of federalism refers us to the issue of a state comprising numerous nations, languages, cultures and religions. Modern democracy is both a political ideology and a political system. It generates increasing dissatisfaction with the way it operates on a practical level. The choice between a unitary and a federal approach does not mean a choice between a democratic or nondemocratic system, yet, from the long-term historical perspective, it appears that a federal system cannot operate without democracy, despite the obvious tensions between a democratic ideal and political reality.